Praticabilidade, obrigações acessórias e as garantias constitucionais do cidadão-contribuinte - Florencio, Madja de Sousa Moura (2016)
The phenomenon of practicality, seen as a means of simplifying laws, is essential to the modern world. The issue gains importance in the present day, with complex relationships held in mass society, which require the use of increasingly modern instruments to materialize commands. The issue has more relevance in the taxpaying field, where practicality appears as essential to the efficiency of state revenue collection device. This paper aims at pointing out, through bibliographical research, constitutionally imposed limits on the use of practicality, in order to show that this principle is mainly turned over to reaching fair taxing and not just for the sake of simplifying the State taxation activity